The impact of behavioral design and users' choice on smartphone app usage and willingness to pay: A framed field experiment - Christina Timko; Maja Adena (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2026)
Behavioral design in smartphone apps aims at inducing certain, monetizable behavior, mainly increased engagement, measurable by usage time. Such design is rarely transparent and often restricts users' ability to make alternative choices. In a framed field experiment, we document that behavioral design doubles app usage time compared to a version without behavioral elements. Providing users with choices-simply explained and conveniently adjustable design features-reduces usage time and increases their willingness to pay for the app. These findings suggest that offering choice could pave the way for new business models based on more responsible app design.
Additional information: This is a revised version of the WZB Discussion Paper SP II 2023-302 "Transparent app design reduces excessive usage time and increases willingness to pay compared to common behavioral design: a framed field experiment", originally published by the same authors within the Research Unit Economics of Change.
Keywords: C93; O33; D83; L86; M14; 330; smartphone app; behavioral control; filtering algorithm; transparency and choice; self-determination; corporate social responsibility; field experiment